Indonesian Defense Industrial Cooperation With The United Arab Emirates In A Defense Economic Perspective - Ria Anggun Arian; Sri Sundari; Lukman Yudho Prakoso (Return : Study of Management, Economic and Bussines, 2023)
The implementation of the defense offset mechanism for the procurement of defense equipment has been going on since the early 1960s, although it was effectively only carried out when IPTN, PT. PAL, and PT. PINDAD established cooperation with the state of arms producers and strategic industries in the mid-1970s. The government's policy for cooperation with the United Arab Emirates in the field of defense industry will be very profitable and also equally build a defense economy and also this cooperation is centered on Joint Marketing for CN235 and N219 aircraft, as well as Joint Development for upgrading versions of N219 aircraft and MALE Black Eagle UAVs, along with Engineering, Design & Flight-Testing WorkPackage cooperation in each product development. This cooperation demonstrates the readiness of the domestic industry for the development ofdefense industry products, through three Defense Industry SOEs, in the form of Joint Marketing cooperation for CN235 multipurpose transport aircraft and N219 light passenger aircraft. The method used in this study is a qualitative method based on the study of in-depth understanding. Qualitative research is a method used to understand the phenomena experienced by the research subject by describing in the form of language, words, and specialnatural contexts.